ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS (BKM) SISWA SMP PADA MATERI SEGIEMPAT DAN SEGITIGA - Khulsum, Regiana; Suryaningsih, Yani; Riajanto, Marchasan L. E. J. (IKIP Siliwangi, 2018)
This research is motivated by the importance of mathematic critical thinking ability for students and the low ability of students matematics critical thinking. The population in this study were all students of SMPN 2 Cimahi class VII, while the sample was students of class VII-7. Then through observation and interview determined 6 students as research subjects. The method used in this study is analytic descriptive. The research instrument is 5 essay questions that represent indicators of mathematic critical thinking ability. The results showed that the average achievement of students in each indicator was less than 50%, which means it can be concluded that students' critical thinking skills are still relatively low.